Prior or concurrent radiotherapy and nivolumab immunotherapy in non–small cell lung cancer. Issue 1 (12th November 2019) - Ratnayake, Gishan; Shanker, Mihir; Roberts, Kate; Mason, Robert; Hughes, Brett G. M.; Lwin, Zarnie; Jain, Vikram; O'Byrne, Kenneth; Lehman, Margot; Chua, Benjamin
Abstract: Background: Studies suggest that combining radiotherapy (RT) with programmed cell death protein 1 (PD‐1) blockade may elicit a synergistic antitumor response. We aimed to assess whether prior or concurrent RT was associated with improved disease control in patients with metastatic non–small cell lung cancer (NSCLC) treated with nivolumab. Methods: We conducted a retrospective study of patients receiving nivolumab as second or subsequent line therapy for metastatic NSCLC. Patients were categorized into those who received any RT for NSCLC prior to or during nivolumab therapy, and those with no history of RT for NSCLC. Results: A total of 85 patients received nivolumab between July 2015 and December 2016 and were followed up for a median of 15 months. Sixty‐five patients (76.4%) received RT prior to or during nivolumab and 20 patients (23.6%) received nivolumab alone. Baseline characteristics of age, performance status, histology, smoking status and previous therapy were similar between the two groups. Prior or concurrent RT was associated with a superior PFS, median 2.8 months with RT versus 1.3 months without RT (Hazard Ratio (HR) = 0.494; 95% Confidence Interval (CI), 0.279–0.873; P  = 0.02). The median OS of the group receiving RT was 6.4 months versus 4.2 months for the no RT group ( P  = 0.20). RT was not associated with an increase in toxicity. Conclusion: RT prior to or concurrent with nivolumab for metastatic NSCLC was associated with a modest improvement in PFS over nivolumab alone with no evidence of increase in adverse effects. RT may potentiate the effect of anti–PD‐1 immunotherapy in NSCLC.